Comparing the Two Techniques for Nursing Staff Rescheduling to Streamline Nurse Managers' Daily Work in Finland. Issue 3 (March 2020) - Tuominen, Outi; Lundgren-Laine, Heljä; Teperi, Simo; Salanterä, Sanna
Abstract : The aim of this study was to identify nurse managers' daily tasks during the rescheduling of sudden nursing staff absences by comparing two techniques: a paper-based system as phone calls and emails or information technology–based staffing systems. In addition, it is intended to evaluate the usability of information technology–based staffing solutions and evaluate estimated cost savings by using hospital permanent staff to cover sudden absences. A quasi-experimental pretest and posttest one-group study design was used to evaluate nurse managers' (n = 61) daily tasks (n = 5800) during rescheduling nursing staff sudden absences (n = 2628); furthermore, we engaged in observations and provided estimates of cost savings generated by our proposed intervention. The number of nurse manager tasks during rescheduling decreased significantly ( P < .001) as well as unstaffed shifts ( P < .001) and unplanned shift changes ( P < .001) after the information technology–based scheduling system was implemented. The usability score ranged from 76 to 100, showing that the information technology–based scheduling solution has good usability. The use of information technology–based staffing solution can streamline the rescheduling process, save nurse managers time for other activities, and offer organizations opportunities for cost savings.